Low-Level Knowledge and Associated Factor of Sexual and Reproductive Health Rights Among Aksum University Students, Aksum Ethiopia - Elsa Tesfa Berhe; Mlite Ayene; Tsigehana Gebregyorgis; Merhawit Gebremeskel Hagos; Teferi Gebru Gebremeskel; Teferi Gebru Gebremeskel (Frontiers Media S.A., 2022)
BackgroundReproductive health rights in Africa are unknown. According to international studies, reproductive health rights of young people particularly university students, are violated, and most of these violations go unreported due to a lack of information and awareness of these rights. The aim of this study was to assess the level of knowledge and associated factors on sexual and reproductive health rights in Ethiopia.MethodsInstitution-based cross-sectional study using an interviewer-administered and structured questionnaire was conducted. The study population consisted of students of the selected department between November, 2018 and June, 2019. A simple random sampling method technique was used to select 420 students. Bi-variate and multi-variate logistic regression analysis was performed.ResultsThe knowledge level of the respondents was 16.4%. The majority of students 205 (51%) were in the age group < 20 years. Male [AOR: 1.46, 95% CI: 1.09-1.95]; coming from urban areas [AOR: 2.11, 95% CI: (1.02-4.37)]; provision of sexuality education or lecture in departments [AOR: 1.39, 95% CI: 1.02-1.91] and discussion about reproductive health with anyone else [AOR: 2.31, 95% CI: 1.48-3.62] were significant association for the knowledge of sexual and reproductive health rights.ConclusionsRespondents' knowledge level was found to be very low. Therefore, strengthening students' lectures or education on reproductive health in the curricula of high school, encouraging discussions with parents, and anyone might improve the knowledge toward sexual and reproductive health rights.